Weird kid - Van Eekhout, Greg (Harper, an imprint of HarperCollins Publishers, 2021)
Jake Foster, a shapeshifting alien of goo disguised as a human, and his spunky friend Agnes investigate the mysterious takeover of their neighbors by "imblobsters" and uncover the reason Jake is losing control of his ability to keep his human shape.